Analisis Pengendalian Kualitas Produk untuk Meminimumkan Produk Gagal pada Pabrik Roti Prabu Bakery - Friscila, Nia; Tunjang, Hansly; Syamsudin, Achmad (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2020)
Purpose, - This study aims to provide an explanation of the implementation of product quality control carried out by Prabu Bakery.Design/methodology/approach - The research method used in this research is quantitative research. The unit of analysis in this research is the bread products produced by Prabu Bakery as many as 54,720 pieces of bread. The collected data were analyzed using the Statistical Quality Control (SQC) approach, the software used was Microsoft Excel 2016. Findings - The results of this study indicate that product quality control at Prabu Bakery has not been able to minimize failed products, so it requires training and development for URL products that fail at Prabu Bakery